Betahistine metabolites, Aminoethylpyridine, and Hydroxyethylpyridine increase cochlear blood flow in guinea pigs in vivo. (October 2014) - Bertlich, Mattis; Ihler, Fritz; Sharaf, Kariem; Weiss, Bernhard G.; Strupp, Michael; Canis, Martin
Abstract Objective: Betahistine is a histamine-like drug that is used in the treatment of Ménière's disease. It is commonly believed that betahistine increases cochlear blood flow and thus decreases the endolymphatic hydrops that is the cause of Ménière's. Despite common clinical use, there is little understanding of the kinetics or effects of its metabolites. This study investigated the effect of the betahistine metabolites aminoethylpyridine, hydroxyethylpyridine, and pyridylacetic acid on cochlear microcirculation. Design: Guinea pigs were randomly assigned to one of the groups: placebo, betahistine, or equimolar amounts of aminoethylpyridine, hydroxyethylpyridine, or pyridylacetic acid. Cochlear blood flow and mean arterial pressure were recorded for three minutes before and 15 minutes after treatment. Study sample: Thirty Dunkin-Hartley guinea pigs assigned to one of five groups with six guinea pigs per group. Results: Betahistine, aminoethylpyridine, and hydroxyethylpyridine caused a significant increase in cochlear blood flow in comparison to placebo. The effect seen under aminoethylpyridin was greatest. The group treated with pyridylacetic acid showed no significant effect on cochlear blood flow. Conclusion: Aminoethylpyridine and hydroxyethylpyridine are, like betahistine, able to increase cochlear blood flow significantly. The effect of aminoethylpyridine was greatest. Pyridylacetic acid had no effect on cochlear microcirculation.